Erratum to: Echoes of 2HDM inflation at the collider experiments - Modak, Tanmoy; Oda, Kin-ya (The European physical journal. C, Particles and fields, 2021)
A correction to this paper has been published: https://doi.org/10.1140/epjc/s10052-020-08450-5
Gesehen am 09.08.2021